Pengaruh Penyuluhan Kesehatan Tentang Posyandu Terhadap Pengetahuan Ibu Balita di Wilayah Kerja Puskesmas Lubuk Durian Kecamatan Kerkap Bengkulu Utara - Elsi Rahmadani; Marlin Sutrisna (Yayasan Literasi Sains Indonesia, 2022)
Integrated service center is one of the government programs related to basic services related to health efforts in preventing infant and under-five mortality. The purpose of this study was to determine the effect of health education on Posyandu on the knowledge of mothers under five in the working area of ​​the Lubuk Durian Health Center, Kerkap District, North Bengkulu. The method used is an analytical research design with a pre and post one group Quasi Experiment approach. The sample in this study amounted to 23 mothers who have toddlers at the Lubuk Durian Argamakmur Health Center. This study uses SPSS with Wilcoxon bivariate statistical test with a value of = <0.05. The results of the univariate analysis showed that the average value of knowledge about posyandu before the Posyandu counseling was 5.30 with a standard deviation of 2.032 and the average value of knowledge after health education about posyandu was 12.87 with a standard deviation of 2.16. The results of the bivariate analysis showed that there was an effect of Health Counseling on Posyandu on Mother Toddler Knowledge in the Working Area of ​​the Lubuk Durian Health Center, Kerkap District, North Bengkulu. The conclusion is that there is an effect of Health Counseling on Posyandu on Mother Toddler Knowledge in the Work Area of ​​the Lubuk Durian Health Center, Kerkap District, North Bengkulu. Researchers suggest that puskesmas are expected to provide information about health, especially about Posyandu for toddlers in the Lubuk Durian Argamakmur Health Center Work Area.